Balance of power; Beatty memorial lectures - Beloff, Max (London, 1968)
Balance of Power' is a convenient term to explain the changing alignments between groups of rival countries. Far from being suspect in its connotation, it is a permanent, necessary, and healthy aspect of international politics. Indeed, the absence of power in some parts of the world leads to imbalance between the centres that exist elsewhere, and hence to dangerous rivalries. The author reviews the history of Europe since 1945, assess the gains and losses entpting to shifts by the of power. He then examines other parts of the world, with special emphasis on the southern rim of Asia as an area where there exists a vacuum of power locally and where difficulties of establishing a balance are at their most acute. In the light of these problems, Professor Beloff recalls the various efforts made to create international organizations as an alternative to reliance on the balance of power. He indicates why success in this field has been so limited and in what circumstances the balance of power could institutionalized. an eminent authority. analysis by A remarkableceivably be Max Beloff is Gladstone Professor of Government 1 Public Administration, University of Oxford, and a Fellow of All Souls College, Oxford.